The Influence of Environmental Factors on the Diversity of Gastropods in Marsegu Island, Maluku - Wiwien Bula; Fredy Leiwakabessy; Dominggus Rumahlatu (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Gastropods are known to have a wide distribution. They can live in a variety of habitats and influenced by various environmental factors. The aim of this study was to investigate the diversity of gastropods and its relationship with the physical and chemical environment of a water. This research was an ecological research with correlational descriptive type. The selection of Marsegu Island was based on the fact that the area is a conservation area, both the forest and sea are frequently visited by tourists. The results of this research showed that there were 22 species of gastropod found in the water of Marsegu Island. The most commonly found was from the genus of Cypraea (5 species). Gastropods found mostly from the family of Strombidae which consisted of 4 genera i.e. Lambis, Canarium, Strombus and Lentigo. The value of gastropod diversity in the three research stations was moderate, 2.93, 2.91 and 2.95 respectively. In addition, there is a correlation between environmental factors and the diversity of gastropods. The simultaneous effect of the independent variables toward the dependent variables can be explained by the magnitude of the determination coefficient (R Square) which was 0528 or 52.8%. Result of this study confirms that the environmental factors greatly affects the diversity of Gastropod in the coastal waters of Marsegu island. The results can provide benefits as control over fishing and coastal pollution due to human activities.